ANALISIS KUALITAS PENCAHAYAAN DAN AKUSTIK PADA BANGUNAN GEREJA KATEDRAL - Khuluk, Nazaruddin; Nikson, Wifan (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
Church is a human need, architecture accommodates worship activities with worship buildings in architecture not only means being able to accommodate worship activities, but must have a great value, for example by displaying ceilings and pillars that are very high and impressive. Buildings that have a much larger proportion than the proportion of the human body willstimulate feelings that make humans feel very small. This feeling isdeliberately presented and often found in the design of places of worship,making people who are inside feel small and are exposed to something bigger.This feeling of